Class and social capital in Europe: a transnational analysis of the European Social Survey - Carmo, R. (2014)
This paper seeks to understand the way in which social capital resources are incorporated, appropriated and distributed by different social classes in Europe. Its main goal is to produce a conceptual framework by linking the concepts of social capital with the different theoretical assessments made by the sociology of social classes. We use multivariate analysis to work a set of quantitative indicators from the European Social Survey 2008 in order to assess the relationship between these concepts. Our methodological approach combines transnational levels, i.e., it is not an international comparison between European countries but an analysis of individual people and their belonging to social classes.